A retinal contribution to opioid-induced sleep disorders? - Bergum, Nikolas; Berezin, Casey-Tyler; Vigh, Jozsef (Frontiers in Neuroscience, 2022)
Chronic opioid use is linked to persistent and severe sleep/wake disturbances in patients. These opioid-related sleep problems increase risk for developing opioid dependence, mood disorders and in turn overdose in chronic pain patients receiving opioid therapy. Despite the well-established link between long-term opioid use and sleep disorders, the mechanism by which opioids perturb sleep remains unclear. Interestingly, animal studies indicate that opioids disrupt sleep/wake behaviors by altering an animal’s ability to synchronize their circadian rhythms to environmental light cycles (ie. photoentrainment). A specific subset of retinal cells known as intrinsically photosensitive retinal ganglion cells (ipRGCs) that express µ-opioid receptors are exclusively responsible for transmitting environmental light information to sleep/circadian centers in the brain. Thus, this review will focus on the effect of opioids on ipRGCs and their projection regions that are involved in the photoentrainment of sleep/wake behaviors. Lastly, we discuss the viability of ipRGCs as a potential therapeutic target for treating opioid-related sleep/wake problems.